Correlation between diagnostic endoscopy, computed tomography and operative findings in patients with chronic rhinosinusitis - Bagewadi, Satish; Ankle, N. R.; Patil, R. N.; Havaldar, Rajesh Radhakrishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The varied symptomatology and diagnostic difficulties pose a great challenge to the Otorhinolaryngologists in treating chronic rhinosinusitis. Both diagnostic nasal endoscopy and computed tomography (CT) has been used to analyse the pathological/anatomical changes associated with chronic rhinosinusitis. Various studies have been done to evaluate the efficacy of both these methods to analyse the changes associated with chronic rhinosinusitis. In this study, the authors contemplate to determine which one is better as a preoperative diagnostic tool. Methods: In this study 30 patients (60 sides) suffering from chronic rhinosinusitis underwent functional endoscopic Sinus Surgery after being thoroughly evaluated by diagnostic endoscopy and CT scan. The various factors affecting the sinus drainage were analysed and compared between each modality. Results: The findings of diagnostic endoscopy correlated very well with the operative findings except for conditions where there was severe anatomic or pathologic obstruction which hampered visualisation. Extent of disease in each sinus is very well recognised on CT. Conclusions: Both diagnostic endoscopy and CT are important preoperative evaluation tools in detecting anatomic variations or pathologic changes within sinuses, although for the surgeon, the operative findings remain the gold standard in the management of the disease.